Laminated optical film
By employing a specific ratio of stacked optical film structure in the foldable display panel, and utilizing a soft second adhesive layer to mitigate tensile stress, the problem of uneven display during bending is solved, ensuring the adhesion of the optical film and improving the image display quality of the display.
Patent Information
- Application Number
- CN202511159815.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-30
- Filing Date
- 2022-04-28
- Publication Date
- 2025-11-18
AI Technical Summary
In foldable display panels, the optical films at the bending points of the laminated optical films experience photoelasticity due to tensile stress, causing uneven display. In particular, the birefringence caused by the hardness of the adhesive layer leads to uneven display issues during long-term use.
A stacked optical film structure is adopted, wherein the compressive elastic modulus of the first adhesive layer and the second adhesive layer satisfies the relationship 0.3≤E2/E1<1. The compressive elastic modulus E2 of the second adhesive layer is less than that of the first adhesive layer. This structure can suppress display non-uniformity by mitigating tensile stress and ensure the bonding force between the optical films.
It effectively suppresses uneven display when the foldable display panel is bent, and the soft second adhesive layer alleviates tensile stress, ensures the adhesion of the optical film, reduces the peeling and bending of the optical film, and improves the image display quality of the display.
Smart Images

Figure CN120963156A_ABST
Abstract
Description
[0001] This application is a divisional application of the application filed on April 28, 2022, with application number 202280022924.4 and invention title "Laminated Optical Film". Technical Field
[0002] This invention relates to laminated optical films. Background Technology
[0003] Display panels, for example, have a stacked structure including a pixel panel, a touch panel, a surface protector, etc. The stacked structure of the display panel also includes various functional optical films having a given optical function. Examples of functional optical films include polarizing films and retardation films. The functional optical films are introduced into the stacked structure, for example, in a state where their two sides are bonded to other optical films such as protective films via adhesives, i.e., in the form of stacked optical films. Such stacked optical films are described, for example, in Patent Document 1 below.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-147865 Summary of the Invention
[0007] The problem the invention aims to solve
[0008] For example, progress has been made in the development of repeatedly bendable (foldable) display panels for use in smartphones and tablet terminals. In foldable display panels, the elements in the laminated structure are made to be repeatedly bendable. Furthermore, at the bending point of the foldable display panel, the optical film located on the outer side of the bend in the laminated optical films experiences tensile stress. This tensile stress has historically caused photoelasticity in the outer optical film at the bending point, resulting in birefringence of light transmitted from the film. Birefringence of transmitted light is a cause of uneven image display on the display panel, which is undesirable. When foldable display panels are used with prolonged repeated bending, the aforementioned birefringence caused by the hardness of the adhesive layer located on the outer side of the bend is particularly prone to causing uneven display.
[0009] The present invention provides a laminated optical film suitable for suppressing display unevenness when a foldable display panel is bent.
[0010] Problem Solving Methods
[0011] The present invention [1] includes a laminated optical film having, in the thickness direction, a first optical film, a first adhesive layer, a second optical film, a second adhesive layer, and a third optical film, wherein the first adhesive layer is bonded to the first optical film and to the second optical film, the second adhesive layer is bonded to the second optical film and to the third optical film, and the compressive elastic modulus E1 of the first adhesive layer at 25°C and the compressive elastic modulus E2 of the second adhesive layer at 25°C satisfy 0.3≤E2 / E1<1.
[0012] The present invention [2] includes the laminated optical film described in [1] above, wherein the indented elastic modulus E2 is 4 GPa or less.
[0013] The present invention [3] includes the laminated optical film described in [1] or [2] above, wherein the indented elastic modulus E2 is 0.4 GPa or above.
[0014] The present invention [4] includes the laminated optical film described in any one of [1] to [3] above, wherein the indented elastic modulus E1 is 0.5 GPa or above.
[0015] The present invention [5] includes the laminated optical film described in any one of [1] to [4] above, wherein the indented elastic modulus E1 is 7 GPa or less.
[0016] The present invention [6] includes any of the above-mentioned [1] to [5] stacked optical films, wherein the above-mentioned second optical film is a polarizing film.
[0017] The effects of the invention
[0018] In the laminated optical film of the present invention, as described above, the compressive elastic modulus E1 of the first adhesive layer and the compressive elastic modulus E2 of the second adhesive layer satisfy 0.3 ≤ E2 / E1 < 1. The second adhesive layer has the following flexibility: its elastic modulus E2 is so small that the ratio (E2 / E1) is less than 1. Such a second adhesive layer is suitable for mitigating the tensile stress generated by the third optical film at the bending point when the laminated optical film is bent with the third optical film as the bending outer side. At the bending point of the third optical film, due to the mitigation of tensile stress, the aforementioned photoelastic effect is reduced, and uneven display of the image on the display panel can be suppressed. In addition, the second adhesive layer having a large compressive elastic modulus E2 with a ratio (E2 / E1) of 0.3 or more is suitable for ensuring the bonding force between the second and third optical films at the bending point. Attached Figure Description
[0019] Figure 1 This is a cross-sectional schematic diagram of one embodiment of the stacked optical film of the present invention.
[0020] Figure 2 Show Figure 1 The image shows the state of the stacked optical film being bent.
[0021] Symbol Explanation
[0022] X-layer optical film
[0023] 10 Optical film (2nd optical film)
[0024] 21 Optical Film (First Optical Film)
[0025] 22 Optical film (3rd optical film)
[0026] 31. Adhesive layer (first adhesive layer)
[0027] 32 Adhesive Layers (Second Adhesive Layer)
[0028] H-thickness direction
[0029] B bend section Detailed Implementation
[0030] like Figure 1 As shown, the stacked optical film X, as one embodiment of the stacked optical film of the present invention, includes an optical film 10, optical films 21 and 22, and adhesive layers 31 and 32. Specifically, the stacked optical film X sequentially includes an optical film 21 (first optical film), an adhesive layer 31 (first adhesive layer), an optical film 10 (second optical film), an adhesive layer 32 (second adhesive layer), and an optical film 22 (third optical film) in the thickness direction H. The stacked optical film X has a sheet shape of a given thickness and is unfolded in a direction orthogonal to the thickness direction H (plane direction). The adhesive layer 31 bonds the optical films 10 and 21 together. The adhesive layer 32 bonds the optical films 10 and 22 together. Furthermore, the stacked optical film X is a composite film introduced into the stacked structure of a foldable display panel. The stacked optical film X is, for example, a stacked optical film disposed on the image display side surface of a display panel such as a foldable organic EL panel (OLED panel). In foldable display panels, stacked optical films X, such as Figure 2 As shown, it is bent with the optical film 21 and adhesive layer 31 as the inside. At the bending portion B, the optical film 21 and adhesive layer 31 are located on the inside of the bend relative to the optical film 10 (lower side in the figure), and the optical film 22 and adhesive layer 32 are located on the outside of the bend relative to the optical film 10 (upper side in the figure).
[0031] In this embodiment, the optical film 10 is a functional optical film. Examples of functional optical films include polarizing films and phase refraction films.
[0032] Examples of polarizing film include hydrophilic polymer films that have undergone dyeing with a dichroic substance and subsequent stretching. Examples of dichroic substances include iodine and dichroic dyes. Examples of hydrophilic polymer films include polyvinyl alcohol (PVA) films, partially methyl acetalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers. Polyene-oriented films can also be used as polarizing film. Examples of materials for polyene-oriented films include dehydrated PVA and dehydrochlorinated polyvinyl chloride. From the perspective of excellent optical properties such as polarization characteristics, PVA films that have undergone dyeing with iodine and subsequent uniaxial stretching are preferred as polarizing film.
[0033] From the viewpoint of thinness, the thickness of the optical film 10, which serves as the polarizing lens film, is preferably 15 μm or less, more preferably 12 μm or less, even more preferably 10 μm or less, and particularly preferably 8 μm or less. Thin polarizing lenses have excellent visual clarity due to less thickness variation, and also exhibit excellent durability against thermal shock due to minimal dimensional changes caused by temperature variations. From the viewpoint of strength, the thickness of the optical film 10, which serves as the polarizing lens film, is preferably 3 μm or more, more preferably 5 μm or more.
[0034] Examples of phase retardation films include, for example, λ / 2 wavelength films, λ / 4 wavelength films, and viewing angle compensation films. Examples of materials for phase retardation films include, for example, polymer films that have undergone birefringence through stretching. Examples of polymer films include, for example, cellulose films and polyester films. Examples of cellulose films include, for example, cellulose triacetate films. Examples of polyester films include, for example, polyethylene terephthalate films and polyethylene naphthalate films. The thickness of the optical film 10, as a phase retardation film, is, for example, 20 μm or more, and for example, 150 μm or less. Furthermore, as a phase retardation film, a film having a substrate such as a cellulose film and an alignment layer of a liquid crystal compound such as a liquid crystal polymer on that substrate is preferably used.
[0035] Optical films 21 and 22 are both transparent protective films. The transparent protective films are, for example, flexible transparent resin films. Examples of materials used for the transparent protective films include: polyolefins, polyesters, polyamides, polyimides, polyvinyl chloride, polyvinylidene chloride, cellulose, modified cellulose, polystyrene, and polycarbonate. Examples of polyolefins include: cyclic olefin polymers (COP), polyethylene, polypropylene, ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, and ethylene-vinyl alcohol copolymers. Examples of polyesters include: polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate. Examples of polyamides include: polyamide 6, polyamide 6,6, and some aromatic polyamides. Examples of modified cellulose include: cellulose triacetate. These materials can be used alone or in combination of two or more. From a cleanliness perspective, polyolefins are preferred as materials for the transparent protective films, and COPs are more preferred. Furthermore, the materials of optical film 21 and optical film 22 can be the same or different.
[0036] From the viewpoint of the strength of the stacked optical film X, the thickness of each of the optical films 21 and 22 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. From the viewpoint of thinning the stacked optical film X, the thickness of the optical film 21 is preferably 100 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less. The thickness of the optical film 21 and the thickness of the optical film 22 may be the same or different.
[0037] Adhesive layer 31 is a cured product of the first adhesive composition. Adhesive layer 31 is directly bonded to optical film 10 and directly bonded to optical film 21. The first adhesive composition contains a curable resin, the specific components of which are described below.
[0038] From the viewpoint of bonding strength between optical films 10 and 21, the thickness T1 of adhesive layer 31 is preferably 0.1 μm or more, more preferably 0.4 μm or more, further preferably 0.7 μm or more, and particularly preferably 0.8 μm or more. From the viewpoint of thinning the laminated optical film X, the thickness T1 of adhesive layer 31 is preferably 5 μm or less, more preferably 3 μm or less, further preferably 1.5 μm or less, and particularly preferably 1 μm or less.
[0039] The compressive modulus E1 of the adhesive layer 31, measured by nanoindentation at 25°C, is preferably 0.5 GPa or more, more preferably 1 GPa or more, further preferably 1.5 GPa or more, and particularly preferably 2 GPa or more. This configuration is preferred for ensuring the bonding force between the optical films 10 and 21 at the bending portion B when the laminated optical film X is bent with the optical film 21 side as the inside. The compressive modulus E1 is preferably 7 GPa or less, more preferably 6 GPa or less, and further preferably 5.2 GPa or less. This configuration is preferred for mitigating the compressive stress acting on the adhesive layer 31 at the bending portion B. The mitigation of compressive stress in the adhesive layer 31 at the bending portion B helps to suppress peeling between the optical films 10 and 21. Furthermore, this configuration, related to the upper limit of the compressive elastic modulus E1, is preferable for ensuring low elasticity in the adhesive layer 31 (the adhesive layer on the inner side of the bend) at the aforementioned bending portion B, thereby achieving sufficient adhesion to the optical films 10 and 21. Therefore, it is suitable for suppressing buckling of the optical film 10 at the bending portion B. As a method for adjusting the compressive elastic modulus E1 of the adhesive layer 31, for example, adjusting the composition of the first adhesive composition can be cited. Specifically, as a method for adjusting the compressive elastic modulus E1 of the adhesive layer 31, adjusting the number of functional groups of the polymeric compound described later in the first adhesive composition, i.e., adjusting the acrylic equivalent and epoxy equivalent of the polymeric compound, is effective.
[0040] Nanoindentation is a technique for measuring various physical properties of a sample at the nanoscale. In this embodiment, nanoindentation is performed based on ISO 14577. In nanoindentation, the process of pressing an indenter into a sample placed on a stage (load application process) and then removing the indenter from the sample (load release process) is performed. During this series of processes, the load acting between the indenter and the sample, and the relative displacement of the indenter relative to the sample are measured (load-displacement measurement), thereby obtaining a load-displacement curve. Based on this load-displacement curve, various physical properties of the sample can be determined based on nanoscale measurements. For example, the load-displacement measurement of the adhesive layer cross-section using nanoindentation can be performed using a nanoindenter (trade name "Triboindenter", manufactured by Hysitron Corporation), as described in the examples below.
[0041] Adhesive layer 32 is a cured product of the second adhesive composition. Adhesive layer 32 is directly bonded to optical film 10 and directly bonded to optical film 22. The second adhesive composition contains a curable resin, the specific components of which are described below.
[0042] From the viewpoint of bonding strength between optical films 10 and 22, the thickness T2 of adhesive layer 32 is preferably 0.1 μm or more, more preferably 0.4 μm or more, further preferably 0.7 μm or more, and particularly preferably 0.8 μm or more. From the viewpoint of thinning the laminated optical film X, the thickness T2 of adhesive layer 32 is preferably 5 μm or less, more preferably 3 μm or less, further preferably 1.5 μm or less, and particularly preferably 1 μm or less. The thickness T2 of adhesive layer 32 may be the same as or different from the thickness T1 of adhesive layer 31 described above. In addition, the ratio of thickness T2 to thickness T1 (T2 / T1) is, for example, 0.5 or more, and, for example, 2 or less.
[0043] The indentation modulus E2 of the adhesive layer 32, as measured by nanoindentation at 25°C, is less than the indentation modulus E1, preferably 0.4 GPa or more, more preferably 0.8 GPa or more, further preferably 1.2 GPa or more, and particularly preferably 1.8 GPa or more. The indentation modulus E2 is less than the indentation modulus E1, preferably 4 GPa or less, more preferably 3 GPa or less, and further preferably 2.5 GPa or less. These configurations are preferred for ensuring the bonding strength between the optical films 10 and 22. As a method for adjusting the indentation modulus E2 of the adhesive layer 32, for example, adjusting the composition of the second adhesive composition can be considered. Specifically, as a method for adjusting the indentation modulus E2 of the adhesive layer 32, adjusting the number of functional groups of the polymeric compound in the second adhesive composition (described later), i.e., adjusting the acrylic equivalent and epoxy equivalent of the polymeric compound, is effective.
[0044] The compressive elastic modulus E1 of adhesive layer 31 at 25°C and the compressive elastic modulus E2 of adhesive layer 32 at 25°C satisfy 0.3≤E2 / E1<1.
[0045] The adhesive layer 32 has a degree of softness such that its compressive modulus E2 is so small that the ratio (E2 / E1) is less than 1. This adhesive layer 32 is suitable for mitigating the tensile stress generated in the optical film 22 at the bending point B when the laminated optical film X is bent with the optical film 22 as the bending outer side. By mitigating the tensile stress at the bending point of the optical film 22, the photoelastic effect is reduced, thereby suppressing display unevenness in the image display of the display panel. From this viewpoint, the ratio (E2 / E1) is preferably 0.97 or less, more preferably 0.8 or less.
[0046] Furthermore, an adhesive layer 32 with a large compressive modulus E2 having a ratio (E2 / E1) of 0.3 or higher is suitable for ensuring the bonding force between the optical films 10 and 22 at the bending portion B. Conversely, an adhesive layer 31 with a small compressive modulus E1 having a ratio (E2 / E1) of 0.3 or higher is preferable for ensuring low elasticity in the adhesive layer 31 at the bending portion B (the adhesive layer on the inner side of the bend) to achieve sufficient adhesion with the optical films 10 and 21, thus suppressing buckling of the optical film 10 at the bending portion B. From these viewpoints, a ratio (E2 / E1) of 0.5 or higher is preferred, and more preferably 0.6 or higher.
[0047] As a method for adjusting the ratio (E2 / E1), examples include adjusting the indented elastic modulus E1 and adjusting the indented elastic modulus E2.
[0048] In the laminated optical film X, the 90° peel strength F1 between optical film 21 and optical film 10 at 25°C is preferably 0.8 N / 15 mm or more, more preferably 1 N / 15 mm or more, further preferably 1.2 N / 15 mm or more, and particularly preferably 1.5 N / 15 mm or more. This configuration is preferred for ensuring good adhesion between optical films 10 and 21, especially for ensuring adhesion between optical films 10 and 21 at the bending portion B when the laminated optical film X is bent. Additionally, the 90° peel strength F1 is, for example, 10 N / 15 mm or less. The 90° peel strength F1 can be measured using the method described in the later embodiments. The peel strength between optical film 21 and optical film 10 is the force required to peel optical film 21 from optical film 10, including interfacial peeling between optical film 10 and adhesive layer 31, peeling caused by the coagulation and destruction of adhesive layer 31, interfacial peeling between adhesive layer 31 and optical film 21, and peeling based on a combination thereof. Furthermore, as a method for adjusting the 90° peel strength F1, one example is adjusting the composition of the first adhesive composition. Specifically, one method for adjusting the 90° peel strength F1 is adjusting the number of functional groups of the polymeric compound (described later) in the first adhesive composition, i.e., adjusting the acrylic equivalent and epoxy equivalent of the polymeric compound.
[0049] In the laminated optical film X, the 90° peel strength F2 between the optical film 22 and the optical film 10 at 25°C is preferably 0.8 N / 15 mm or more, more preferably 1 N / 15 mm or more, further preferably 1.2 N / 15 mm or more, and particularly preferably 1.5 N / 15 mm or more. This configuration is preferred for ensuring good adhesion between the optical films 10 and 22, and particularly for ensuring adhesion between the optical films 10 and 22 at the bending portion B when the laminated optical film X is bent. Additionally, the 90° peel strength F2 is, for example, 10 N / 15 mm or less. The 90° peel strength F2 can be measured by the method described in the later embodiments. The peel strength between the optical film 22 and the optical film 10 is the force required to peel the optical film 22 from the optical film 10, including interfacial peeling between the optical film 10 and the adhesive layer 32, peeling caused by the coagulation and destruction of the adhesive layer 32, interfacial peeling between the adhesive layer 32 and the optical film 22, and peeling based on a combination thereof. Furthermore, as a method for adjusting the 90° peel strength F2, one example is adjusting the composition of the second adhesive composition. Specifically, one method for adjusting the 90° peel strength F2 is adjusting the number of functional groups of the polymeric compound (described later) in the second adhesive composition, i.e., adjusting the acrylic equivalent and epoxy equivalent of the polymeric compound.
[0050] The adhesive layer 31 is, for example, a cured product of a first adhesive composition (a first active energy ray-curable composition) containing an active energy ray-curable resin. Examples of the first active energy ray-curable composition include electron beam curable compositions, ultraviolet curable compositions, and visible light curable compositions. In this embodiment, the first active energy ray-curable composition is either a free radical polymerization composition or a cationic polymerization composition, or both.
[0051] When the first active energy ray-curable composition is a free radical polymerizable composition, the composition contains a free radical polymerizable compound as a monomer. A free radical polymerizable compound is a compound having a free radical polymerizable functional group. Examples of free radical polymerizable functional groups include groups containing olefinic unsaturated bonds. Examples of groups containing olefinic unsaturated bonds include (meth)acryloyl, vinyl, and allyl. (Methacryl)acryloyl refers to acryloyl and / or methacryloyl. From the viewpoint of the curability of the first active energy ray-curable composition, the first active energy ray-curable composition preferably contains a free radical polymerizable compound having a (meth)acryloyl group as a main component, where the main component is the component with the highest content by mass percentage. The proportion of the free radical polymerizable compound containing a (meth)acryloyl group in the first active energy ray-curable composition is, for example, 50% by mass or more, preferably 70% by mass or more, and more preferably 80% by mass or more. In addition, examples of free radical polymerizable compounds include monofunctional free radical polymerizable compounds and polyfunctional free radical polymerizable compounds with two or more functions.
[0052] Examples of monofunctional free radical polymerizable compounds include (meth)acrylamide derivatives having a (meth)acrylamide group. Examples of (meth)acrylamide derivatives include: N-alkyl (meth)acrylamide derivatives, N-hydroxyalkyl (meth)acrylamide derivatives, N-aminoalkyl (meth)acrylamide derivatives, N-alkoxy (meth)acrylamide derivatives, and N-mercaptoalkyl (meth)acrylamide derivatives. Examples of N-alkyl (meth)acrylamide derivatives include: N-methyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-hexyl (meth)acrylamide, with N,N-diethylacrylamide being preferred. Examples of N-hydroxyalkyl (meth)acrylamide derivatives include N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and N-hydroxymethyl-N-propyl (meth)acrylamide, with N-hydroxyethylacrylamide being preferred. The (meth)acrylamide derivatives can be used alone or in combination of two or more.
[0053] Examples of monofunctional free radical polymerizable compounds include (meth)acrylic acid derivatives having a (meth)acryloyloxy group. Examples of such (meth)acrylic acid derivatives include alkyl (meth)acrylates and other (meth)acrylic acid derivatives. (Methacryl)acrylic acid derivatives can be used alone or in combination of two or more.
[0054] Examples of alkyl methacrylates include: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, 2,2-dimethylbutyl methacrylate, n-hexyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, 4-methyl-2-propylpentyl methacrylate, and n-octadecyl methacrylate.
[0055] Examples of (meth)acrylic acid derivatives other than alkyl (meth)acrylates include: cycloalkyl (meth)acrylates, aralkyl (meth)acrylates, hydroxyl-containing (meth)acrylic acid derivatives, alkoxy (meth)acrylic acid derivatives, and phenoxy (meth)acrylic acid derivatives. Examples of cycloalkyl (meth)acrylates include: cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate. Examples of aralkyl (meth)acrylates include: benzyl (meth)acrylate and 3-phenoxybenzyl (meth)acrylate. Examples of hydroxyl-containing (meth)acrylic acid derivatives include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, [4-(hydroxymethyl)cyclohexyl]methyl acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate. Examples of alkoxy (meth)acrylic acid derivatives include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and 3-methoxybutyl (meth)acrylate. Examples of phenoxy (meth)acrylic acid derivatives include phenoxyethyl (meth)acrylate and phenoxydiethylene glycol (meth)acrylate. As a (meth)acrylic acid derivative other than alkyl (meth)acrylates, at least one selected from 3-phenoxybenzyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate, and phenoxydiethylene glycol acrylate is preferred.
[0056] Monofunctional free radical polymerizable compounds can also include carboxyl-containing monomers. Examples of carboxyl-containing monomers include: (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, butenoic acid, and isobutenoic acid.
[0057] Examples of monofunctional free radical polymerizable compounds include lactam vinyl monomers. Examples of lactam vinyl monomers include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone.
[0058] Examples of monofunctional radical polymerizable compounds include vinyl monomers having nitrogen-containing heterocycles. Examples of such monomers include: vinylpyridine, vinylpiperidinone, vinylpyrimidine, vinylpiperazine, vinylpyrrazine, vinylpyrrole, vinylimidazolium, and vinylpyrrole. Azole, acryloylmorpholine, and vinylmorpholine.
[0059] As multifunctional free radical polymerizable compounds, for example, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecanediethanol di(meth)acrylate, cyclotrimethylolpropane methyl acetal (meth)acrylate, di... Alkanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, preferably tripropylene glycol diacrylate and neopentyl glycol hydroxypivalate acrylate adduct. As a multifunctional radical polymerizable compound, at least one selected from tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, and neopentyl glycol hydroxypivalate acrylate adduct is preferred. The multifunctional radical polymerizable compound can be used alone or in combination of two or more. The multifunctional radical polymerizable compound functions as a crosslinking agent.
[0060] When the first active energy ray-curable composition is an ultraviolet-curable composition or a visible light-curable composition, the first active energy ray-curable composition preferably contains a photopolymerization initiator. Examples of photopolymerization initiators include: benzophenone compounds, benzoin ether compounds, and thioxanone compounds. Examples of benzophenone compounds include: benzoyl, benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone. Examples of benzoin ether compounds include: benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin butyl ether. Examples of thioxanone compounds include: thioxanone, 2-chlorothioxanone, 2-methylthioxanone, 2,4-dimethylthioxanone, isopropylthioxanone, 2,4-dichlorothioxanone, 2,4-diethylthioxanone, 2,4-diisopropylthioxanone, and dodecylthioxanone.
[0061] When the first active energy ray curable composition is a visible light curable composition, a photopolymerization initiator with high sensitivity to light above 380 nm is preferably used. Examples of such photopolymerization initiators include: 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(n5-2,4-cyclopentadien-1-yl)bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium.
[0062] 2,4-Diethylthioxanone and / or 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one are preferred as photopolymerization initiators.
[0063] In the first active energy ray curable composition, the content of photopolymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of curable component (free radical polymerizable compound).
[0064] When the first active energy ray-curable composition is a cationic polymeric composition, the composition contains a cationic polymerizable compound as a monomer. A cationic polymerizable compound is a compound having a cationic polymerizable functional group, including monofunctional cationic polymeric compounds having one cationic polymerizable functional group and polyfunctional cationic polymeric compounds having two or more cationic polymerizable functional groups. Monofunctional cationic polymeric compounds have relatively low liquid viscosity; by incorporating such a monofunctional cationic polymeric compound into the resin composition, the viscosity of the resin composition can be reduced. Furthermore, monofunctional cationic polymeric compounds generally possess functional groups exhibiting various functions. By incorporating such a monofunctional cationic polymeric compound into the resin composition, the resin composition and / or the cured resin composition can exhibit various functions. On the other hand, by curing a resin composition incorporating a polyfunctional cationic polymeric compound, a cured product with a three-dimensional cross-linked portion can be obtained (where the polyfunctional cationic polymeric compound functions as a cross-linking agent). From this viewpoint, the use of a polyfunctional cationic polymeric compound is preferred. When a monofunctional cationic polymeric compound is used in combination with a polyfunctional cationic polymeric compound, the amount of the polyfunctional cationic polymeric compound relative to 100 parts by mass of the monofunctional cationic polymeric compound is, for example, 10 parts by mass or more, and, for example, 1000 parts by mass or less. Examples of cationic polymeric functional groups include epoxy groups, oxetyl groups, and vinyl ether groups. Examples of compounds containing epoxy groups include aliphatic epoxy compounds, alicyclic epoxy compounds, and aromatic epoxy compounds. From the viewpoint of the curability and adhesion of the cationic polymeric composition, alicyclic epoxy compounds are preferred as compounds containing epoxy groups. Examples of alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, or caprolactone-modified, trimethylcaprolactone-modified, and valproicone-modified versions of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate. Commercially available alicyclic epoxy compounds include, for example, CELLOXIDE 2021, CELLOXIDE 2021A, CELLOXIDE 2021P, CELLOXIDE 2081, CELLOXIDE 2083, and CELLOXIDE 2085 (all manufactured by CELLOXIDE Chemical Co., Ltd.), and Cyracure UVR-6105, Cyracure UVR-6107, Cyracure 30, and R-6110 (all manufactured by Dow Chemical Japan Ltd.). From the viewpoint of improving the curability and reducing the viscosity of cationic polymeric compositions, compounds having oxocyclic butyl groups and / or compounds having vinyl ether groups are preferred.Examples of compounds containing oxetane include: 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetane)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, di[(3-ethyl-3-oxetane)methyl] ether, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and phenolic varnish oxetane. Commercially available examples of compounds containing oxetane include: ARON OXETANE OXT-101, ARON OXETANE OXT-121, ARON OXETANE OXT-211, ARON OXETANE OXT-221, and ARON OXETANE OXT-212 (all manufactured by Toa Synthetic Co., Ltd.). Examples of compounds having a vinyl ether group include: 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, triethylene glycol divinyl ether, cyclohexanediethanol divinyl ether, cyclohexanediethanol monovinyl ether, tricyclodecane vinyl ether, cyclohexyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, and pentaerythritol-type tetravinyl ether.
[0065] When the first active energy ray-curable composition is an ultraviolet-curable composition or a visible light-curable composition, the first active energy ray-curable composition contains a photocationic polymerization initiator. The photocationic polymerization initiator generates cationic species or Lewis acids upon irradiation by active energy rays (visible light, ultraviolet light, X-rays, electron beams, etc.), thereby initiating a polymerization reaction of cationic polymerizable functional groups. Examples of photocationic polymerization initiators include photoacid generators and photoalkali generators, with photoacid generators being preferred. When the first active energy ray-curable composition is a visible light-curable composition, a photocationic polymerization initiator with high sensitivity to light above 380 nm is particularly preferred. Furthermore, when using a photocationic polymerization initiator, it is preferable to combine it with a photosensitizer that exhibits significant absorption for wavelengths longer than 380 nm. Photocationic polymerization initiators are compounds that typically exhibit maximum absorption in the wavelength region around 300 nm or shorter than 300 nm. Therefore, by combining photosensitizers that exhibit maximum absorption under light with wavelengths longer than 380 nm, it is possible to effectively utilize light with wavelengths longer than 380 nm to promote the generation of cationic species or Lewis acids from the photocationic polymerization initiator. Examples of photosensitizers include anthracene compounds, pyrene compounds, carbonyl compounds, organosulfur compounds, persulfides, redox compounds, azo compounds, diazo compounds, halogen compounds, and photoreducing pigments. These can be used alone or in combination of two or more. Anthracene compounds are particularly preferred due to their excellent photosensitizing effect. Commercially available anthracene compounds used as photosensitizers include, for example, Anthracure UVS-1331 and Anthracure UVS-1221 (manufactured by Kawasaki Chemical Co., Ltd.). The content of the photosensitizer in the composition is, for example, 0.1 to 5% by weight.
[0066] The first active energy ray-curable composition may contain oligomers. Examples of oligomers include acrylic oligomers, fluoro oligomers, and silicone oligomers, with acrylic oligomers being preferred. The inclusion of oligomers in the first active energy ray-curable composition helps to suppress shrinkage during curing. Suppression of curing shrinkage in the first active energy ray-curable composition is preferred for reducing interfacial stress between the formed adhesive layer 31 and the optical films 10, 21, and suppression of interfacial stress helps to ensure adhesion between the optical films 10, 21.
[0067] Examples of (meth)acrylic acid monomers that form acrylic acid oligomers include, for example, alkyl (meth)acrylic acid esters, cycloalkyl (meth)acrylic acid esters, aralkyl (meth)acrylic acid esters, polycyclic (meth)acrylic acid esters, hydroxyl-containing (meth)acrylic acid esters, and halogen-containing (meth)acrylic acid esters. Examples of alkyl methacrylates include: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, 2-methyl-2-nitropropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, tert-pentyl methacrylate, 3-pentyl methacrylate, 2,2-dimethylbutyl methacrylate, n-hexyl methacrylate, hexadecyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, 4-methyl-2-propylpentyl methacrylate, and n-octadecyl methacrylate. Examples of cycloalkyl methacrylates include: cyclohexyl methacrylate and cyclopentyl methacrylate. Examples of aralkyl methacrylates include: benzyl methacrylate. Examples of polycyclic (meth)acrylates include: 2-isoborneol (meth)acrylate, 2-norborneol methyl (meth)acrylate, 5-norbornen-2-yl methyl (meth)acrylate, and 3-methyl-2-norborneol methyl (meth)acrylate. Examples of hydroxyl-containing (meth)acrylates include: hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2,3-dihydroxypropyl methylbutyl (meth)acrylate. Examples of halogen-containing (meth)acrylates include: 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethyl ethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, and heptadecafluorodecyl (meth)acrylate. These (meth)acrylates can be used alone or in combination of two or more.
[0068] The weight-average molecular weight (Mw) of the acrylic oligomer is preferably 15,000 or less, more preferably 10,000 or less, and even more preferably 5,000 or less. The Mw of the acrylic oligomer is preferably 500 or more, more preferably 1,000 or more, and even more preferably 1,500 or more.
[0069] The content of acrylic oligomers in the first active energy ray-curable composition is preferably 2% by mass or more, more preferably 4% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less.
[0070] The first active energy ray curable composition may contain other components. Examples of other components include silane coupling agents, leveling agents, surfactants, plasticizers, and ultraviolet absorbers. The amount of these other components relative to 100 parts by weight of the curable component is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, even more preferably 3 parts by weight or less, and, for example, 0.01 parts by weight or more.
[0071] From the viewpoint of coatability in the coating process described later, the viscosity of the first active energy ray-curable composition at 25°C is preferably 3 mPa·s or more, more preferably 5 mPa·s or more, and even more preferably 10 mPa·s or more. Furthermore, it is preferably 100 mPa·s or less, more preferably 50 mPa·s or less, and even more preferably 30 mPa·s or less. The viscosity of the composition is measured using an E-type viscometer (cone-plate viscometer).
[0072] The adhesive layer 32 is, for example, a cured product of a second adhesive composition containing an active energy ray-curable resin (an active energy ray-curable composition). Examples of the second active energy ray-curable composition include electron beam curable compositions, ultraviolet curable compositions, and visible light curable compositions. Among these, the second active energy ray-curable composition and the first active energy ray-curable composition can be of the same type or different types. Furthermore, in this embodiment, the second active energy ray-curable composition is a free radical polymerizable composition.
[0073] As a component of the second active energy ray-curable composition, the aforementioned components, which are also components of the first active energy ray-curable composition, may be used. The content range of the component in the second active energy ray-curable composition is the same as the content range of the component in the first active energy ray-curable composition described above. The composition of the second active energy ray-curable composition may be the same as or different from that of the first active energy ray-curable composition.
[0074] The laminated optical film X can be manufactured, for example, as described below.
[0075] First, a first active energy ray-curable composition is coated onto one side (the bonding predetermined side) of the optical film 21 to form a first coating film of the composition (first coating step). Then, a second active energy ray-curable composition is coated onto one side (the bonding predetermined side) of the optical film 22 to form a second coating film of the composition (second coating step). Before each coating step, the bonding predetermined side of the optical film may undergo surface modification treatment. Examples of surface modification treatments include corona treatment, plasma treatment, excimer laser treatment, and flame treatment. Examples of coating methods used in this process include, for example, reverse coating, gravure coating, bar reverse coating, roll coating, die coating, wire rod coating, and bar coating.
[0076] Next, optical film 21 is laminated to one side of optical film 10 with the first coating in between, and optical film 22 is laminated to the other side of optical film 10 with the second coating in between. The lamination can be performed, for example, using a roller laminator that performs both laminations simultaneously.
[0077] Next, the first coating and the second coating are irradiated with active energy rays, causing the first coating to cure and form an adhesive layer 31, and the second coating to cure and form an adhesive layer 32 (adhesive layers 31 and 32 are not pressure-sensitive adhesive layers). Thus, optical films 10 and 21 are bonded together through adhesive layer 31, and optical films 10 and 22 are bonded together through adhesive layer 32.
[0078] In this process, from the viewpoint of suppressing the deterioration of the optical film 10, which is a functional optical film, it is preferable to irradiate the first coating with active energy rays from the optical film 21 side and the second coating with active energy rays from the optical film 22 side. Electron beams, ultraviolet light, and visible light can be used as active energy rays. An electron beam irradiation device can be, for example, an electron beam accelerator. Examples of sources of ultraviolet and visible light include LED lamps, gallium-encapsulated metal halide lamps, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, and gallium lamps. In this process, wavelength blocking filters can be used as needed to block a portion of the wavelength range of ultraviolet and / or visible light emitted from the light source.
[0079] The laminated optical film X can be manufactured, for example, as described above.
[0080] Example
[0081] The present invention will be specifically described below with reference to embodiments, but the present invention is not limited to the embodiments. In addition, the specific numerical values of the amount (content), physical property value, parameter, etc. described below can be replaced with the upper limit (a value defined in the form of "less than" or "less than") or lower limit (a value defined in the form of "more than" or "exceeds") of the amount (content), physical property value, parameter, etc. described in the "Specific Embodiments" above.
[0082] [Example 1]
[0083] The following components were mixed at 25°C for 1 hour according to the proportions shown in Table 1 (proportions based on solid content), thereby preparing a first adhesive composition for a first adhesive layer (first preparation step). Furthermore, the following components were mixed at 25°C for 1 hour according to the proportions shown in Table 1 (proportions based on solid content), thereby preparing a second adhesive composition for a second adhesive layer (second preparation step). The proportions shown in Table 1 are in parts by mass.
[0084] LIGHT ACRYLATE POB-A (monomer): 3-phenoxybenzyl acrylate, manufactured by Kyoei Chemical Co., Ltd.
[0085] LIGHT ACRYLATE P2H-A (monomer): Phenoxy diethylene glycol acrylate, manufactured by Kyoei Chemical Co., Ltd.
[0086] Aronix M-5700 (monomer): 2-hydroxy-3-phenoxypropyl acrylate, manufactured by Toa Synthetic Co., Ltd.
[0087] Aronix M-220 (monomer): Tripropylene glycol diacrylate, manufactured by Toa Synthetic Co., Ltd.
[0088] HEAA (monomer): Hydroxyethylacrylamide, manufactured by KJ Chemical Co., Ltd.
[0089] DEAA (monomer): Diethylacrylamide, manufactured by KJ Chemical Co., Ltd.
[0090] OMINIRAD907 (photopolymerization initiator): 2-Methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, manufactured by IGM Resins.
[0091] KAYACURE DETX-S (Photopolymerization Initiator): 2,4-Diethylthioxanthone, manufactured by Nippon Kayaku Co., Ltd.
[0092] Arufon 1190 (acrylic acid oligomer): viscosity 6000 mPa·s (25℃), Mw 1700, Tg -50℃, manufactured by Toa Synthetic Co., Ltd.
[0093] BYK-UV3505 (leveling agent): A modified polydimethylsiloxane with acryloyl groups, manufactured by BYK Corporation.
[0094] Next, the coating process is performed, as detailed below. A first adhesive composition is applied to a 23μm thick COP film (trade name "ZEONOR Film ZF14", manufactured by Zeon Corporation, Japan) serving as the first transparent protective film, forming a 1μm thick first adhesive coating. Conversely, a second adhesive composition is applied to a 23μm thick COP film (trade name "ZEONOR Film ZF14", manufactured by Zeon Corporation, Japan) serving as the second transparent protective film, forming a 1μm thick second adhesive coating. Each coating is performed using an MCD coating machine (manufactured by Fuji Machinery Co., Ltd.) (cell shape honeycomb, gravure roller line count 1000 lines / inch, rotation speed 140% / line speed).
[0095] Next, the first transparent protective film with the first adhesive coating, the polarizing lens film, and the second transparent protective film with the second adhesive coating were laminated (lamination process). Specifically, a roller laminator was used to laminate the first adhesive coating side of the first transparent protective film to one side of the polarizing lens film, and the second adhesive coating side of the second transparent protective film to the other side of the polarizing lens film.
[0096] Next, ultraviolet light is irradiated onto the first adhesive coating from the first transparent protective film side, and ultraviolet light is irradiated onto the second adhesive coating from the second transparent protective film side, thereby curing the adhesive coating between the films (curing process). The ultraviolet irradiation uses an ultraviolet irradiation device (trade name "LightHAMMER10", valve: V valve, manufactured by Fusion UV Systems, Inc.) equipped with a gallium-encapsulated metal halide lamp as the light source. During ultraviolet irradiation, the peak illuminance is set to 1600 mW / cm². 2 Set the cumulative exposure dose to 1000 mJ / cm². 2 (Wavelength 380~440nm) (Illuminance was measured using the "Sola-Check System" manufactured by Solatell). Thus, the first transparent protective film and the polarizing lens film are bonded together via the first adhesive layer, and the second transparent protective film and the polarizing lens film are bonded together via the second adhesive layer, thereby obtaining a laminated optical film.
[0097] The laminated optical film of Example 1 was fabricated as described above. The laminated optical film of Example 1 comprises, in the thickness direction, a first transparent protective film (thickness 23 μm), a first adhesive layer, a polarizing lens film (thickness 5 μm), a second adhesive layer, and a second transparent protective film (thickness 23 μm).
[0098]
[0099] [Example 2]
[0100] Except for the operations described below, the laminated optical film of Example 2 (first transparent protective film / first adhesive layer / polarizing film / second adhesive layer / second transparent protective film) was fabricated in the same manner as the laminated optical film of Example 1.
[0101] In the first preparation step, instead of using "LIGHT ACRYLATE POB-A", "LIGHT ACRYLATE P2H-A" and "Aronix M-220", 40 parts by weight of "LIGHT ACRYLATE 1.9ND-A" (1,9-nonanediol diacrylate) manufactured by Kyoeisha Chemical Co., Ltd. and 9 parts by weight of "LIGHT ACRYLATE HPP-A" (hydroxypentanoic acid neopentyl glycol acrylate adduct) manufactured by Kyoeisha Chemical Co., Ltd. are used. The amount of "Aronix M-5700" is set to 22 parts by weight, the amount of "HEAA" is set to 12.5 parts by weight, the amount of "DEAA" is set to 6 parts by weight, the amount of "HEAA" is set to 12.5 parts by weight, and the amount of "Arufon 1190" is set to 10 parts by weight. In addition, in the coating process, the thickness of the first adhesive layer coating film formed on the first transparent protective film is set to 1.1 μm, and the thickness of the second adhesive layer coating film formed on the second transparent protective film is set to 1.2 μm.
[0102] [Example 3]
[0103] Except for the operations described below, the laminated optical film of Example 3 (first transparent protective film / first adhesive layer / polarizing lens film / second adhesive layer / second transparent protective film) was fabricated in the same manner as the laminated optical film of Example 1.
[0104] In the first preparation step, instead of using "LIGHT ACRYLATE POB-A", "Aronix M-220", "Aronix M-5700", "DEAA" and "Arufon 1190", 27 parts by mass of "LIGHT ACRYLATE 1.9ND-A" (1,9-nonanediol diacrylate) manufactured by Kyoei Chemical Co., Ltd. and 59 parts by mass of "ACMO-LI" (acryloylmorpholine) manufactured by KJ Chemical Co., Ltd. are used. The amount of "LIGHT ACRYLATE P2H-A" is set to 10 parts by mass and the amount of "HEAA" is set to 3 parts by mass. In the second preparation step, the amount of "LIGHT ACRYLATE POB-A" is set to 43 parts by mass, the amount of "LIGHT ACRYLATE P2H-A" is set to 29 parts by mass, the amount of "Aronix M-220" is set to 3 parts by mass, and the amount of "Aronix M-5700" is set to 10 parts by mass. Furthermore, in the coating step, the thickness of the first adhesive layer coating formed on the first transparent protective film is set to 1.2 μm, and the thickness of the second adhesive layer coating formed on the second transparent protective film is set to 0.9 μm.
[0105] [Comparative Example 1]
[0106] Except for the operations described below, a composite optical film (first transparent protective film / first adhesive layer / polarizing lens film / second adhesive layer / second transparent protective film) of Comparative Example 1 was fabricated in the same manner as the composite optical film of Example 1.
[0107] In the first preparation step, the same composition as the second adhesive composition in Example 1 was prepared. In the second preparation step, instead of "LIGHT ACRYLATE POB-A", "Aronix M-220", "Aronix M-5700", "DEAA", and "Arufon 1190", 23 parts by weight of "LIGHT ACRYLATE 1.9ND-A" (1,9-nonanediol diacrylate) manufactured by Kyoei Chemical Co., Ltd. and 60 parts by weight of "ACMO-LI" (acryloylmorpholine) manufactured by KJ Chemical Co., Ltd. were used. The amount of "LIGHT ACRYLATE P2H-A" was set to 13 parts by weight and the amount of "HEAA" was set to 3 parts by weight. In addition, in the coating step, the thickness of the first adhesive layer coating film formed on the first transparent protective film was set to 1.0 μm, and the thickness of the second adhesive layer coating film formed on the second transparent protective film was set to 1.2 μm.
[0108] <Thickness of adhesive layer>
[0109] The thickness T of each adhesive layer in each of the laminated optical films of Examples 1-3 and Comparative Example 1 was measured as follows. First, a 5 mm × 10 mm film sheet (laminated optical film) was cut from the laminated optical film. Next, the laminated optical film was cut by cryosectioning. Specifically, the laminated optical film was cooled to -30°C, and then cut along the thickness direction of the film with a hard blade. After being restored to room temperature, a conductive treatment with a thickness of less than 5 nm was performed on the cut surface of the laminated optical film, thereby obtaining an observation sample. Next, the thickness of the adhesive layer was measured by SEM observation of the observation sample. Specifically, a secondary electron image of the cut surface in the observation sample was observed and captured using a scanning electron microscope (trade name "REGULUS 8220", manufactured by HITACHI Corporation), and the thickness of each adhesive layer was measured. In this observation, the accelerating voltage was set to 3.0 kV, the current to 10 μA, the working distance to 8 mm, the magnification to 100,000 times, and the detection mode to Upper+Lower mode. The thicknesses T1 (μm) of the first adhesive layer and T2 (μm) of the second adhesive layer are shown in Table 2, as is the ratio of thickness T2 to thickness T1 (T2 / T1).
[0110] <Peel strength>
[0111] The 90° peel strength between the first transparent protective film and the polarizing film in each of the laminated optical films of Examples 1-3 and Comparative Example 1 was measured as follows (First Measurement). First, a first sample film with dimensions of 200 mm on the first side and 15 mm on the second side was cut from the laminated optical film. The first side is the side extending in the stretching direction of the polarizing film, and the second side is the side extending in a direction orthogonal to the stretching direction. Next, the second transparent protective film side of the first sample film was bonded to a glass plate with a strong adhesive. Next, the 90° peel strength (N / 15 mm) of the first transparent protective film from the polarizing film was measured using a Tensilon universal testing machine (trade name "RTC", manufactured by A&D Corporation). In this measurement, the glass plate and the first sample film from the glass plate to the polarizing film on the glass plate were held by the first chuck of the Tensilon universal testing machine, and the first transparent protective film of the first sample film was held by the second chuck of the testing machine. In addition, in this test, the test temperature was set to 25°C, the peel angle was set to 90°, and the peel speed was set to 1000 mm / min. Table 2 shows the 90° peel strength F1 (N / 15 mm) in this peel test when the first transparent protective film was peeled from the polarizing lens film.
[0112] In addition, the 90° peel strength between the second transparent protective film and the polarizing film in each of the laminated optical films of Examples 1-3 and Comparative Example 1 was measured as follows (Second Measurement). First, a second sample film identical to the first sample film was cut from the laminated optical film. Next, the first transparent protective film side of the second sample film was bonded to a glass plate with a strong adhesive. Next, the 90° peel strength (N / 15mm) between the second transparent protective film and the polarizing film was measured using a Tensilon universal testing machine (trade name "RTC", manufactured by A&D Corporation). In this measurement, the glass plate and the second sample film from the glass plate to the polarizing film on the glass plate were held by the first chuck of the Tensilon universal testing machine, and the second transparent protective film of the second sample film was held by the second chuck of the testing machine. The measurement conditions in the second measurement were the same as those in the first measurement. Table 2 shows the 90° peel strength F2 (N / 15mm) in the peel test of peeling the second transparent protective film from the polarizing lens film.
[0113] <Indented elastic modulus>
[0114] The indentation modulus of the first adhesive layer in each of the laminated optical films of Examples 1-3 and Comparative Example 1 was determined by nanoindentation. Specifically, firstly, a 5mm × 10mm film (laminated optical film) was cut from the laminated optical film; next, the laminated optical film was cut by cryosectioning, specifically, the laminated optical film was cooled to -30°C, then cut along the thickness direction of the film with a hard blade, and then restored to room temperature, thereby obtaining the sample for testing. Next, the load-displacement of the exposed surface of the adhesive layer of the test sample was measured using a nanoindenter (trade name "TI950 Triboindenter", manufactured by Hysitron Corporation) based on JISZ 2255:2003, and the load-displacement curve was obtained. In this measurement, the measurement mode was set to single indentation measurement, the measurement temperature was set to 25℃, the indenter was set to a Berkovich (triangular pyramid) diamond indenter, the maximum indentation depth (maximum displacement hmax) of the indenter to the test sample during the load application process was set to 50nm, the indentation speed of the indenter was set to 10nm / s, and the withdrawal speed of the indenter from the test sample during the load release process was set to 10nm / s. The obtained measurement data were then processed using the dedicated analysis software (Ver. 9.4.0.1) of the "TI950 Triboindenter". Specifically, based on the obtained load (f)-displacement (h) curve, the maximum load fmax (the load acting on the indenter at the maximum displacement hmax), the contact projection area S (the projected area of the contact region between the indenter and the sample at maximum load), and the slope D of the tangent line of the load-displacement curve at the start of the load release process were obtained. Then, the indentation elastic modulus of the first adhesive layer (=(π)) was calculated based on the slope D and the contact projection area S. 1 / 2 D) / (2S 1 / 2 The value of this value is shown in Table 2 as the indentation elastic modulus E1 (GPa).
[0115] In addition, the indentation elastic modulus of the second adhesive layer in each of the laminated optical films of Examples 1 to 3 and Comparative Example 1 was measured in the same manner as the indentation elastic modulus E1 of the first adhesive layer. This value is shown in Table 2 as the indentation elastic modulus E2 (GPa), and the ratio of the indentation elastic modulus E2 to the indentation elastic modulus E1 (E2 / E1) is also shown in Table 2.
[0116] <Discrete Display>
[0117] With the laminated optical films of Examples 1-3 and Comparative Example 1 installed on a display panel, the presence or absence of display unevenness when the display panel was bent was investigated. An organic EL panel (OLED panel) taken from a commercially available foldable smartphone was used as the display panel. The laminated optical film was disposed on the image display side surface of the display panel. Specifically, the second transparent protective film side of the laminated optical film was adhered to the image display side surface of the display panel via adhesive. Then, with an image displayed on the display panel, the display panel was bent 90°, and the image at the bent portion was observed visually. Cases where no display unevenness (color variation) was observed in the image at the bent portion were rated as "good," and cases where display unevenness was observed were rated as "bad." The results are shown in Table 2.
[0118] <High Temperature and High Humidity Bending Test>
[0119] High-temperature and high-humidity bending tests were conducted on each of the laminated optical films of Examples 1-3 and Comparative Example 1 as described below.
[0120] First, evaluation samples were cut from the laminated optical film. Specifically, rectangular samples of 25mm × 100mm were cut from the laminated film, with the absorption axis of the polarizing film in the cut sample parallel to the long side. Next, a bending test was performed on the sample using a planar unloaded U-shaped stretching tester (manufactured by YUASA SYSTEM Co., Ltd.). In this test, bending clamps were installed at both ends of the sample along the long side, within a range of 20mm from the edge of the sample end, fixing the sample to the tester (the central 60mm area along the long side of the sample was not fixed). In addition, in this test, the sample was repeatedly deformed (bent) 80,000 times at a bending speed of 60rpm between a bending shape with the face of the first transparent protective film inside and a non-bending shape. The bending shape in this test specifically refers to the shape in which the axis of the bending thrust acting on the sample is orthogonal to the absorption axis of the polarizing film. Under this bending condition, the bending radius of the sample was set to 3 mm, and the bending angle was set to 180°. Then, regarding the peeling inhibition between the films (first transparent protective film, polarizing lens film, and second transparent protective film) in such a bending test, cases where no peeling occurred between the films after 80,000 bending cycles were evaluated as "good", and cases where peeling occurred after fewer than 80,000 bending cycles were evaluated as "poor". The evaluation results are shown in Table 1.
[0121]
[0122] Industrial applicability
[0123] The laminated optical film of the present invention can be used as an element in the laminated structure of a display panel, such as a foldable display panel.
Claims
1. A laminated optical film, comprising, in a thickness direction, a first optical film, a first adhesive layer, a second optical film, a second adhesive layer, and a third optical film, sequentially. The first adhesive layer is bonded to the first optical film and also to the second optical film. The second adhesive layer is bonded to the second optical film and also to the third optical film. The compressive modulus E1 of the first adhesive layer at 25°C and the compressive modulus E2 of the second adhesive layer at 25°C satisfy 0.3≤E2 / E1<1.
2. The stacked optical film according to claim 1, wherein, The indented elastic modulus E2 is below 4 GPa.
3. The stacked optical film according to claim 1, wherein, The indented elastic modulus E2 is above 0.4 GPa.
4. The stacked optical film according to claim 1, wherein, The indented elastic modulus E1 is above 0.5 GPa.
5. The stacked optical film according to claim 1, wherein, The indented elastic modulus E1 is below 7 GPa.
6. The laminated optical film according to any one of claims 1 to 5, wherein, The second optical film is a polarizing lens film.
Citation Information
Patent Citations
Active energy ray-curable adhesive composition, polarization film and manufacturing method thereof, optical film, and image display unit
JP2019147865A